Psychology: Creating the Future Together - Results of 16th European Congress of Psychology - Regina V Ershova (Peoples' Friendship University of Russia (RUDN University), 2019)
The report contains a brief overview of the 16th European Congress of Psychology (ECP2019), which was held in Moscow at July 2-5, 2019. The congress brought together more than 3,000 delegates from 94 countries of the world and became one of the landmark international events in the ﬁeld of psychology in 2019.